2021
DOI: 10.1080/19420676.2021.1976816
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Social Entrepreneurship in Higher Education: Active Pedagogy in a Deweyan Perspective

Abstract: Social entrepreneurship education has achieved academic recognition as a subject matter and field of research. However, there is no consensus about how this subject should be taught. The paper explores the potential of active pedagogy for social entrepreneurship education, presenting a Deweyan perspective focussed on reflection and ownership of learning. It draws on a three-year interinstitutional project that aimed at disseminating active pedagogy among in-service teachers in Latin America, and it presents th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…In doing so, professors can support students with design thinking principles that are particularly appropriate and useful when starting social enterprises (Kickul et al, 2018). Reflection and critical thinking about real problems in local communities can lead to a greater understanding of society's issues, and networking for future projects (Pischetola & Martins, 2021). At the institutional level, service learning significantly influences environmental sustainability commitment in higher education (Alfirević et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, professors can support students with design thinking principles that are particularly appropriate and useful when starting social enterprises (Kickul et al, 2018). Reflection and critical thinking about real problems in local communities can lead to a greater understanding of society's issues, and networking for future projects (Pischetola & Martins, 2021). At the institutional level, service learning significantly influences environmental sustainability commitment in higher education (Alfirević et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Another study based on a qualitative approach involving interviews with teachers participating in social entrepreneurship courses and focus groups with learners indicates a positive impact of active pedagogy on student empathy (Pischetola & Martins, 2021). The results showed that reflecting on concrete cases of local social problems triggered empathy among students.…”
Section: Antecedents Of Social Entrepreneurship Intention Empathymentioning
confidence: 97%
“…Using experiential learning with income-generating projects also led to the development of communication skills, as well as the generation of new ideas and empathy (Chang et al 2014). Active pedagogy with a perspective focused on reflection has lead to an increase of "social and behavioural competencies" compared to those based on "leadership, making and organisation" (Pischetola & Martins, 2021).…”
Section: Review Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a society marked by inequalities and socio-environmental problems, recently aggravated by the COVID-19 pandemic as recognized in Quantin and Tubert-Bitter (2022) and Serpa and Ferreira (2022), social entrepreneurship succeeds in strengthening the role of education to promote projects and practices that provide students with the chance to recognize their potential to transform and generate positive impact. The challenge of teaching social entrepreneurship has been taken up by several higher education institutions by building specific training programs for it (Pischetola et al , 2021; Pizarro and Graybeal, 2022; Talmage and Gassert, 2022). Knowledge of entrepreneurial intention has been an important element to characterize the impact and achievement of educational programs supporting the teaching of entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%